Disproportionate mitral regurgitation as a predictor of functional outcomes following edge-to-edge repair with the MitraClip system. (14th October 2021) - Maltsinioti Charalampia, C M; Schueler Robert, R S; Lambers Moritz, M L; Eissmann Mareike, M E; Schmitz Thomas, T S; Bruder Oliver, O B
Abstract: Aims: The concept of disproportionate mitral regurgitation (MR) was recently from the analysis of the results of two large randomized trials that compared edge-to-edge repair with the MitraClip system and optimal medical treatment alone in a cohort of patients with functional MR and reduced left ventricular (LV) function. Patients with disproportionate MR were defined as having higher degrees of MR, measured with the effective regurgitant orifice area (EROA), than expected with respect to the amount of LV enlargement, as measured using the enddiastolic volume (EDV). Interestingly, disproportionate MR patients were found to benefit more pronounced from an interventional mitral valve repair than those with proportionate MR with respect to the risk of death and hospitalization for heart failure, and these benefits were paralleled by a relevant decrease in LVEDV. In our study we tested this concept, that was derived from the very controlled setting of a randomized trial, in a "real world" retrospective analysis. Methods and results: 137 patients (mean age 78.4±7, log. EuroScore 24.5±13.8%) with symptomatic functional mitral regurgitation (MR) undergoing MitraClip procedure were included and followed for 6±2 months. All patients were highly symptomatic (NYHA functional class 3 or 4: 94.9%, NT-proBNP 6645.5±7517.8 pg/ml). At baseline left ventricular ejection fraction (LVEF) was 34.4±10% with an EDV of 155.8±66.5 ml. When dividing groups following the proposed concept, we found 46.7% of patients having disproportionate MR with larger EDV (167.2±61.4 ml, 137.6±70.8 ml, p=0.026) and not different EROA values (0.45±0.13 cm 2, 0.44±0.21 cm 2, p=0.59) compared to patients with proportionate MR. When analyzing clinical outcomes after 6 months, we found no difference in mortality (p=0.5) and rehospitalizations for heart failure (p=0.7). Patients in both groups significantly improved in functional NYHA class at discharge (p<0.001, p=0.02, respectively). Of note, in patients with disproportionate MR NYHA class amelioration was sustained even after 6 months of follow up (p=0.4), whereas in patients with proportionate MR NYHA class was significantly worsened (p=0.04) after 6 months compared to evaluation at discharge. Conclusions: We found no difference in mortality or rehospitalizations for heart failure when retrospectively analyzing our patient cohort divided in patients with proportionate and disproportionate MR. Both groups improved directly after MitraClip with respect to functional NYHA class, but only in patients with disproportionate MR this effect was sustained over the period of 6 months follow up. Patients with proportionate MR significantly worsened with respect to functional NYHA class 6 months after MitraClip and this effect is surely prone to lead to a higher rehospitalization rate when expanding follow up time to 12 months or more. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): Elisabeth Krankenhaus Essen